2022
DOI: 10.1039/d2fo01119k
|View full text |Cite
|
Sign up to set email alerts
|

Codonopsis pilosula oligosaccharides modulate the gut microbiota and change serum metabolomic profiles in high-fat diet-induced obese mice

Abstract: Obesity has become a main health problem worldwide, linked to gut microbiota imbalance and chronic inflammation. This study aims to evaluate whether Codonopsis pilosula oligosaccharides (CPO) can alleviate obesity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…CPPs, as an important active ingredient and biomarker of CP( Luan et al, 2021 ; Yue et al, 2023 ), play important pharmacological roles in a wide range of diseases, especially metabolic diseases ( Zhang Y. et al, 2020 ; Bai et al, 2022 ; Chen S. et al, 2024 ), digestive diseases ( Meng et al, 2020 ; Zhou et al, 2024 ), hepatic diseases ( Hu et al, 2022 ; Meng X. et al, 2023 ), neurological diseases ( Wan et al, 2020 ; Hu et al, 2021 ) and respiratory diseases ( Gong et al, 2022 ). In a high-fat/high-sucrose diet-induced mouse model, CPPs led to a decrease in MDA levels and an increase in the ratio of GSH to oxidized GSH, as well as an increase in SOD and CAT, which activated the antioxidant signaling pathway and ameliorated high-fat/high-sucrose diet-induced insulin resistance ( Zhang Y. et al, 2020 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…CPPs, as an important active ingredient and biomarker of CP( Luan et al, 2021 ; Yue et al, 2023 ), play important pharmacological roles in a wide range of diseases, especially metabolic diseases ( Zhang Y. et al, 2020 ; Bai et al, 2022 ; Chen S. et al, 2024 ), digestive diseases ( Meng et al, 2020 ; Zhou et al, 2024 ), hepatic diseases ( Hu et al, 2022 ; Meng X. et al, 2023 ), neurological diseases ( Wan et al, 2020 ; Hu et al, 2021 ) and respiratory diseases ( Gong et al, 2022 ). In a high-fat/high-sucrose diet-induced mouse model, CPPs led to a decrease in MDA levels and an increase in the ratio of GSH to oxidized GSH, as well as an increase in SOD and CAT, which activated the antioxidant signaling pathway and ameliorated high-fat/high-sucrose diet-induced insulin resistance ( Zhang Y. et al, 2020 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“… Sucrose trisaccharide, 2–10 fructose units Regulate gut flora, laxative, anti-cancer, regulate blood sugar Morinda officinalis ( Morinda officinalis F. C. How) Roots of the dicotyledonous plant medicine Rubiaceae. Glucose, galactose, composed of 2–5 monosaccharide molecules Anti-dementia, anti-depression, anti-oxidative stress, memory enhancement, immune enhancement, sexual function enhancement ( Cha et al, 2019 , Chi et al, 2020 ) Jerusalem artichoke ( Helianthus tuberosus L.) Perennial herbs of the genus Sunflower, family Asteraceae Oligofructose, glucose, galactose, consisting of 2–10 monosaccharide molecules Antioxidant, hypolipidemic, regulates gut flora, inhibits weight gain and fat storage American ginseng ( Panax quinquefolius L.) Ginseng perennials, family Cincinnabaraceae Glucose, galactose, arabinose, consisting of 2–10 monosaccharide molecules Antioxidant, hypoglycemic, hypolipidemic Codonopsis pilosula ( Codonopsis Radix ) Dried root of Codonopsis pilosula, family Platycodonaceae Glucose, galactose, arabinose, consisting of 2–10 monosaccharide molecules Antioxidant, anti-aging, beauty ( Bai et al, 2022 , Yue et al, 2023 ) Panax ginseng ( Panax ginseng C. A. Mey.)…”
Section: Herbal Oligosaccharidesmentioning
confidence: 99%
“…It also regulated lipid metabolism of adipose tissues and liver and corrected HFD‐induced dysbiosis by increasing beneficial bacteria ( Bifidobacterium , Lactobacillus , Dobosiella , and Faecalibaculum ) and decreasing harmful bacteria ( Erysipelatoclostridium , Helicobacter , and Mucispirillum ) 104 . Furthermore, supplementation of oligosaccharides from Codonopsis pilosula decreased fat accumulation and body weight and improved glucose tolerance in HFD‐fed obese mice, along with increasing the proportion of the beneficial bacteria Muribaculaceae spp., Alistipes and Clostridium and decreasing the proportion of the harmful bacteria Rikenella , Enterobacteriaceae spp., Collinsella , and Megasphaera 105 …”
Section: Prebiotics and Gut Microbiotamentioning
confidence: 99%
“…104 Furthermore, supplementation of oligosaccharides from Codonopsis pilosula decreased fat accumulation and body weight and improved glucose tolerance in HFD-fed obese mice, along with increasing the proportion of the beneficial bacteria Muribaculaceae spp., Alistipes and Clostridium and decreasing the proportion of the harmful bacteria Rikenella, Enterobacteriaceae spp., Collinsella, and Megasphaera. 105 Moreover, the ingestion of oligofructose has been associated with the improvement of blood glucose and fasting insulin in diabetic rats, as well as the inhibition of appetite in HFD-fed animals. 106 Clinical studies of healthy participants have confirmed the results in animals, demonstrating that the ingestion of oligofructose modulates the concentration of GLP-1, ghrelin, and PYY in humans, reducing the sensation of hunger and postprandial blood glucose changes in these participants.…”
Section: Microbiotamentioning
confidence: 99%